Two different rat models for cardiac hypertrophy by constriction of ascending and abdominal aorta (Journal of Laboratory Animal Science, 2024)
Atherosclerosis is one of the important life style diseases of human beings. There are several animal models in vogue  for studying the patho-physiology of Atherosclerosis. It is usually done by inducing pressure overload of aorta. In  this study we attempted two different murine models by constriction of thoracic aorta (ascending aorta) and by  constriction of abdominal aorta, using metal clips. It was observed that thoracic aorta banding requires expertise,  expensive equipment and an increased mortality rate compared to abdominal aorta banding. But the time period for  the development of cardiac hypertrophy was lesser in thoracic method (2-4 months) compared to abdominal aorta  approach (20-24 months).
Keywords: Atherosclerosis; cardiac hypertrophy; rats; aorta